The Dielectric Breakdown of Magnetic Fluids - Kudelcik, Jozef; Bury, Peter; Zavisova, Vlasta; Timko, Milan; Kopcansky, Peter (Communications - Scientific letters of the University of Zilina, 2010)
The development of dielectric breakdown and the DC dielectric breakdown voltage of magnetic fluids based on inhibited transformer oil ITO 100 were investigated in parallel orientations of external magnetic field. It was shown that the breakdown voltage is strongly influenced by the magnetic nanoparticles. The magnetic fluids with the volume concentration of 1% had better dielectric properties than pure transformer oil. The increase of breakdown voltage was interpreted on the base of the bubble theory of breakdown.